Redesain sarana berkebun hidroponik untuk skala rumah tangga dengan menggunakan teknik Vertikultur - Maulana, Eby; Puspitasari, Ratna (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Gardening belongs to the recent activity or trend that can be done by all ages. In addition, these activities can hinder people from all daily problems and also become healthy routines that can be done on the sidelines of routine work. However, the conditions for urban residents, especially Surabaya has made gardening difficult to do because of limited land. Besides, the high population in Surabaya which reaches 2.7 million people has caused the settlements density increasing. This research concerned with the problem of hydroponic gardening facilities for limited land and household scale by utilizing verticulture hydroponic techniques and modern technology, so that people can implement a healthy lifestyle by consuming and producing organic vegetable products without using pesticides. This study employed a mix method by combining the methods of qualitative (research method based on intensive observation and interviews) and quantitative (research method based on the results of a questionnaire that will become supporting data in the study). Furthermore, the case studies were conducted in 2 places, Surabaya and Sidoarjo. The design applied auto-control and clean design concepts and this research obtained 5 design developments. The final design was resulted from a visual questionnaire; the development of design 4 using a modular system so that it is easy to disassemble and the user will be convenient to apply the product. Next, the production process was carried out within the scale 1:1 and closed with conclusions and suggestions.